N=2 supersymmetry partial breaking and tadpole anomaly - R. Ahl Laamara; M.N. El Kinani; E.H. Saidi; M. Vall (Nuclear Physics B, 2015)
We consider the U(1)n extension of the effective N=2 supersymmetric U(1)×U(1) model of arXiv:1204.2141; and study the explicit relationship between partial breaking of N=2 supersymmetry constraint and D3 brane tadpole anomaly of type IIB string on Calabi–Yau threefolds in presence of HRR and HNS fluxes. We also comment on supersymmetry breaking in the particular N=2U(1) Maxwell theory; and study its interpretation in connection with the tadpole anomaly with extra localised flux sources.